Genetic variability, heritability, correlation and path analysis in fenugreek (Trigonella foenum graecum L.) (Indian Journal of Arid Horticulture, 2018)
Thirty fenugreek genotypes (Trigonella foenum graecumL) were evaluated during rabi season of 2012-13 to explore its  existing gene pool and identify the selection indices with an eye on a more comprehensive breeding programme. Characters like  number of pods per plant, protein content in seed, days to 50% flowering and dry weight at flower initiation were found to have  least variation among the coefficients both at phenotypic and genotypic level. Broad sense heritability estimates were high for  protein content in seed (96.9), followed by number of pods per plant (96.7). The highest genetic advance as percentage of mean  was recorded for dry matter content and dry weight at flower initiation indicating that these characters are governed by additive  gene action. Correlation coefficients at phenotypic and genotypic level envisaged that biological yield was having significant and  positive correlation with chlorophyll content of the leaves, number of pods per plant, straw yield per plant, 1000 seed weight, dry  matter content of the plant as whole and seed yield per plant while negatively correlated with the harvest index. Path coefficient  analysis revealed that biological yield per plant, harvest index, dry weight at flower initiation, chlorophyll content in leaves,  number of branches per plant and 1000 seed weight were the most important characters contributing towards seed yield and hence  purposeful and balanced selection based on these traits would be more rewarding for improvement of fenugreek.
Keywords: Genetic variability; heritability; correlation; path coefficient analysis